ETIKA KOMUNIKASI ISLAM DAN REKAM JEJAK DIGITAL: TELAAH HERMENEUTIKA AKUN MEDIA SOSIAL FUFUFAFA - Maryam Mahasura; Muhammad Gofur; Riky Arista (Fakultas Dakwah Institut Dirosat Islamiyah Al-Amien Prenduan, 2025)
The rapid development of social media has significantly transformed patterns of public communication, including religious expression and Islamic preaching in digital public spaces. Social media no longer functions merely as a medium for information exchange, but also as a digital arena that records every communicative expression in the form of digital footprints. This condition raises ethical concerns, particularly when communication practices involve satire, insinuation, or harsh diction that may undermine others. This article aims to examine digital communication ethics from an Islamic perspective through an analysis of the digital footprints of social media posts from the fufufafa account, which gained widespread public attention. This study employs a qualitative approach using Fazlur Rahman’s hermeneutical method, emphasizing a double movement of interpretation from the historical context of Qur’anic texts to contemporary social realities. The research data were collected through documentation of social media posts that have widely circulated in the digital public sphere. The analysis connects the recorded communication patterns in these posts with Islamic communication ethics, particularly the moral values contained in Qur’an Surah Al-Hujurat verse 11. The findings indicate that the analyzed posts reflect ethically problematic communication practices, characterized by satirical language and symbolic expressions that may provoke negative perceptions in digital interactions. Digital footprints are not merely technological residues but also represent the moral character and ethical responsibility of communication actors. This study contributes to the field of Islamic communication ethics by emphasizing the importance of ethical reflection in social media practices in order to foster a more respectful, responsible, and ethical digital communication environment.